Using thematic analysis to obtain the newly arrived pupil voice: An exploration into the experiences of school for Czech and Slovak secondary-aged pupils - King, Cheryl (2020)
Inclusion is a focus of many UK policy and legislation (DfES 2004b, 2006) giving particular reference to pupils with protected characteristics, such as race (Equality Act, 2010). Newly arrived pupils are shown to exhibit poorer educational and social outcomes (Organisation for Economic Co-operation and Development, 2017; Goulter and Green, 2015), transferring through to their later life (Goodenow, 1993; Haslam et al., 2009). Newly arrived pupils also possess fewer protective factors that support their integration into education in a new country, such as sharing the same language as peers (Hastings, 2012) or possessing a shared cultural identity (Chen, 2009; Wallace, 2011). The current study aimed to develop a deeper understanding of the experiences of school for newly arrived Czech and Slovak young people in United Kingdom (UK) mainstream education. Semi-structured interviews were carried out with four participants within Key Stage 3 provision who had recently moved to the UK from either the Czech Republic or Slovakia. Data were analysed using Thematic Analysis (TA). The researcher identified eight candidate themes which supported the educational experiences of participants. These included a combination of factors ranging from appropriate academic support, developing a peer group and effective home-school communication. In addition, participants reported feeling less able to engage with adults in schools and other Black and Minority Ethnic (BME) peers. Whilst all participants identified establishing positive peer relationships as important to their school experiences, a key finding from this research was the extent to which they felt disconnected from peers and the frequency and severity of bullying they experienced. These experiences appeared to have led to a sense of disaffection with school and concern about absconding and safety. This research highlights the implications for practitioners operating within schools and local authorities, in particular, for Educational Psychologists (EPs). Consideration is given towards the steps the LA, schools and EPSs could take in helping to meet the needs and support school experiences of newly arrived Czech and Slovak young people.